Assessment of the variation in nutritional composition and safety of dried recovered food from United States households and prospects for use in chicken feed - Hill, Geoff; Sayadi, Azita; Gendreau, Joseph D.; Tobar, Zachary; Liu, Yanhong; Pitesky, Maurice E.; Simmons, Christopher W. (Frontiers in Sustainable Food Systems, 2023)
Introduction New poultry feed valorization pathways for recovered household food could be enabled by commercially available household devices that dry uneaten food material, arrest spoilage, and preserve nutrient content. However, the nutrient composition, safety, and feed incorporation potential of dried recovered household food (DRHF) is presently unknown. Methods Thirty-eight households spanning 31 states participated in a 4-to-6-week survey to generate and collect food residues that were dried using an in-home device. The DRHF samples were evaluated for chemical composition, digestibility of energy and amino acids, and safety to determine their potential for inclusion in chicken feed. Results and discussion The DRHF had average levels of 15.9% crude protein, 13.3% crude fat, and 22.6% neutral detergent fiber, and 3.18 kcal/g of nitrogen-adjusted true metabolizable energy (by dry weight). The Windows User-Friendly Feed Formulation 2.1 modeler was used to perform linear programming and develop chicken feed rations for broilers and layers that incorporated DRHF alongside conventional feed ingredients, including corn, soybean meal, dicalcium phosphate, limestone, synthetic amino acids, salt, vitamin premix, and mineral premix. The feed formulation results showed that, on average, DRHF incorporation rates of up to 33 and 37% (by weight) are predicted to avoid any nutrient deficiencies or electrolyte imbalances in the broiler and layer rations, respectively. In the broiler ration, DRHF displaced corn, soybean meal, and limestone to varying degrees, while corn, soybean meal, animal fat, dicalcium phosphate, and limestone were substantially displaced in the layer rations. Addition of vitamin premix was predicted as necessary to facilitate DRHF inclusion in the layer rations. Furthermore, foodborne pathogens, mycotoxins, and heavy metals were either absent or below United States regulatory threshold levels. Measured levels of biogenic amines and fat/oil oxidation were consistent with prior research showing compatibility with chickens. These results can inform future in vivo feeding trials to validate the use of DRHF with varying properties in poultry feed.